P-glycoprotein mediated efflux limits substrate and drug uptake in a preclinical brain metastases of breast cancer model - Adkins, Chris E.; Mittapalli, Rajendar K.; Manda, Vamshi K.; Nounou, Mohamed I.; Mohammad, Afroz S.; Terrrell, Tori B.; Bohn, Kaci A.; Yasemin, Celik; Grothe, Tiffany R.; Lockman, Julie A.; Lockman, Paul R. (Frontiers in Pharmacology, 2013)
The blood-brain barrier (BBB) is a specialized vascular interface that restricts the entry of many compounds into brain. This is accomplished through the sealing of vascular endothelial cells together with tight junction proteins to prevent paracellular diffusion. In addition, the BBB has a high degree of expression of numerous efflux transporters which actively extrude compounds back into blood. However, when a metastatic lesion develops in brain the vasculature is typically compromised with increases in passive permeability (blood-tumor barrier; BTB). What is not well documented is to what degree active efflux retains function at the BTB despite the changes observed in passive permeability. In addition, there have been previous reports documenting both increased and decreased expression of P-gp in lesion vasculature. Herein, we simultaneously administer a passive diffusion marker (14C-AIB) and a tracer subject to P-gp efflux (rhodamine 123) into a murine preclinical model of brain metastases of breast cancer. We observed that the metastatic lesions had similar expression (p>0.05; n=756-1214 vessels evaluated) at the BBB and the BTB. Moreover, tissue distribution of R123 was not significantly (p>0.05) different between normal brain and the metastatic lesion. It is possible that the similar expression of P-gp on the BBB and the BTB contribute to this phenomenon. Additionally we observed P-gp expression at the metastatic cancer cells adjacent to the vasculature which may also contribute to reduced R123 uptake into the lesion. The data suggest that despite the disrupted integrity of the BTB, efflux mechanisms appear to be intact, and may be functionally comparable to the normal BBB. The BTB is a significant hurdle to delivering drugs to brain metastasis.